AI MODEL COLLAPSE AND HUMAN CREATIVITY: BEYOND JACQUES ELLUL'S DYSTOPIA. - Reichard, Joshua D. (Journal of Interdisciplinary Studies, 2025)
Jacques Ellul predicted that technology-driven societies risk losing human agency to autonomous technological systems focused on efficiency ("technique"). This essay assesses critically Ellul's concerns regarding technological dystopia through the narrow context of Generative Artificial Intelligence. While acknowledging valid concerns raised by Ellul and contemporary scholars, the essay contends that Generative AI's inherent limitations will prevent it from realizing such dystopian scenarios. Specifically, Generative AI relies fundamentally on human-generated data, and inevitably suffers from "model collapse," a technical degradation resulting from recursive training on AI-generated content. Consequently, Generative AI lacks the capacity for sustained autonomy and poses minimal longterm threats compared to Agentic AI. An eventual collapse of Generative AI models may catalyze a renaissance of human creativity, and thereby ensure humanity evades Ellul's most dire predictions of a technological dystopia.